O USO DOS OPERADORES METADISCURSIVOS EM TEXTOS DISSERTATIVO- ARGUMENTATIVOS SOB A PERSPECTIVA DE HYLAND: análise de redações de alunos do Ensino Médio do Centro de Ensino Professor Antônio Carlos Beckman- Açailândia-Ma - NASCIMENTO, Ângela Maria do (2024)
This research addresses the importance of metadiscursivity for persuasive purposes in dissertation-argumentative texts and aims to analyze the frequency and rhetorical function of the use of metadiscursive operators in essays of this textual genre. To do this, we selected texts produced by students in the 3rd year of high school, from the Professor Antônio Carlos Beckman Teaching Center, in the Municipality of Açailândia- Ma. The analysis, based on the analytical reading of these texts, sought to verify how metadiscursive operators contribute to the argumentative construction of the text. Hyland's (2005) interpersonal metadiscourse model served as a contribution to support the investigation of the corpus, as well as theoretical foundations based on Hyland (2005b), Hyland (2004), Silva (2017), Sampaio (2010), Koch (2003 ),Koch (2009), Koch (2011), Koch (2015), Marcuschi (2008), Hyland and Tse (2004), Crismore (1985) and Vande Kopple (2012), authors who also address the subject. In relation to teaching written production, such as Antunes (2003), Geraldi (1984) and Bakthin (2003). This research is classified as documentary research, of a basic nature, explanatory in nature and with a quantitative and qualitative approach. To analyze the data, we used the methodological principles of Corpus Linguistics, through the Antconc tool, theoretically anchored by Anthony (2019) and Sardinha (2004). We analyzed the interview given to the teacher, from the series covered, seeking to relate, analogously, the results obtained through the text proposed to the students and the teacher's work practice. As an educational product of this investigation, with the aim of supporting the teacher's work, we present learning suggestions, through an e-book, demonstrating metadiscursive techniques that cover the genre studied, thus ratifying the pedagogical value of this research. We hope that the results achieved prove the effectiveness of metadiscursivity in written production and that they serve as a stimulus for other studies.